2005
DOI: 10.1158/1535-7163.mct-05-0048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of insulin-like growth factor-I receptor (IGF-IR) signaling and tumor cell growth by a fully human neutralizing anti–IGF-IR antibody

Abstract: Insulin-like growth factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 40 publications
4
88
0
1
Order By: Relevance
“…Interestingly, we have recently shown that IGF receptor 1 (IGF-1R) is expressed at a significantly higher level in all ER þ tumors (including ER þ /HER2 þ ) compared with ERÀ/HER2 þ tumors (Appl Immunohistochem Mol Morphol; in press). 40 Similar findings were reported by Harris et al 41 If these findings are also supported by additional studies, IGF-1R may be another molecule that could be targeted with available antibodies [42][43][44][45] in these difficult-to-treat ER þ /HER2 þ tumors, despite the presence of two well-known targets.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, we have recently shown that IGF receptor 1 (IGF-1R) is expressed at a significantly higher level in all ER þ tumors (including ER þ /HER2 þ ) compared with ERÀ/HER2 þ tumors (Appl Immunohistochem Mol Morphol; in press). 40 Similar findings were reported by Harris et al 41 If these findings are also supported by additional studies, IGF-1R may be another molecule that could be targeted with available antibodies [42][43][44][45] in these difficult-to-treat ER þ /HER2 þ tumors, despite the presence of two well-known targets.…”
Section: Discussionsupporting
confidence: 70%
“…SCH 717454 is a fully human neutralizing IgG1 antibody raised against human IGF-IR using Medarex's HuMab mouse technology (34). SCH 717454 was prepared, stored, and diluted in sodium acetate buffer [20 mmol/L sodium acetate, 150 mmol/L NaCl (pH 5.0-5.5)].…”
Section: Reagentsmentioning
confidence: 99%
“…To minimize the potential for immunologic liabilities of non-human antibodies, several fully human monoclonal antibodies against IGF-1R several fully human monoclonal antibodies against IGF-IR have recently been generated (32)(33)(34)(35). These antibodies exhibit potent antitumor effects in breast, colon, prostate, ovarian, and pancreatic cancers in vitro and in vivo and offer great potential for success as safe and effective human anticancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies against the binding domain of IGF-1R block binding of the ligand and subsequent activation of the receptor [31][32][33][34][35][36][37][38]. Binding of these antibodies can trigger receptor internalization and degradation with reduction in the receptor number on the cell surface.…”
Section: Igf-1r Antibodiesmentioning
confidence: 99%